MOTIVASI, PEMBELAJARAN PENGATURAN KENDIRI DAN PRESTASI AKADEMIK- SATU KAJIAN DI KALANGAN PELAJAR ASASI PENGAJIAN ISLAM UNIVERSITI MALAYA NILAM PURI - Mohamad Adnan, Mohamad Azrien; Yusoff, Mohd Alwee (Journal of Al-Tamaddun, 2009)
The aim of this study is to identify the factors that influence academic performance among University of Malaya Pre-Academic of Islamic Studies Students. The study also examines the differences between various factors among them. Those factors are intrinsic value, self-efficacy, test anxiety, cognitive strategy and resource management strategy. The study uses a survey method that make use of a questionnaire as an instrument. The samples consist of 110 second semester up to fourth semester students from University of Malaya Pre-Academic of Islamic Studies Students. Pearson correlation, multiple regression analysis and test are used in this study to investigate the influence of those factors. The result of multiple regression analysis indicated that all factors except for the test anxiety factor are not significantly related in influencing the academic performance.